Uma arquitetura para planejamento e acompanhamento de voo de VANTs em ambientes de multiprojeção - Paiva, Glesio Garcia de (2018)
Nowadays, the use of Unmanned Aerial Vehicles (UAVs), also known as Drones, has grown in several areas, such as military, civilian and entertainment. These vehicles can capture large volumes of data, such as images and telemetry data. One challenge is to address these data and make flight control decisions based on them. Virtual Reality provides the ability to the users to immerse and interact in simulated environments. In this way, enriching the UAVs' user experience with Virtual Reality is a promising possibility for providing an environment that exploits the presentation of a lot of information in a single, immersive and online environment.This work presents how the resources provided by the Virtual Reality can be used in the planning and flight monitoring of UAVs. An architecture for an immersive control station that uses a multiprojection system, called miniCAVE, was proposed to display the video and other information captured by the UAV and transmitted over a 4G network. The proposed architecture enables the flight plan creation containing several waypoints (georeferenced points) as well as tracking the entire route and data of a mission online. Experimental results were obtained to evaluate the video resolution and the telemetry data sent to miniCAVE. These results showed that it is possible to have video resolution that enables a good user experience with bandwidth consumption within the limits found in 4G networks.